Perancangan Alat Pengangkut Telur yang Ergonomis Menggunakan Pendekatan Ergonomi dan Value Engineering - Anwar, Andrian; Hudaningsih, Nurul (Universitas Kadiri, 2024)
Food, especially eggs, is essential and increasingly demanded in Indonesia. High egg consumption in Sumbawa boosts distribution needs, necessitating in-depth ergonomic research to reduce musculoskeletal pain risks for workers. Identifying workload and ergonomic risks is crucial in material handling studies. With %CVL ranging from 14.8%-27.1%, the design of egg-lifting tools and value engineering methodologies are required for cost optimization and safety. This study designs and evaluates ergonomic aids for egg transportation. The quantitative research at UD. Saudaraku, Sumbawa, employs %CVL > 22% and value engineering methods to design ergonomic egg transport tools. The sample includes three workers with a pulse rate > 170 bpm, with measurements taken using a pulse oximeter and MSDs questionnaires. The study identifies issues with manual methods and heavy loads in egg handling, causing fatigue and pain in 100% of workers. Evaluation reveals cardiovascular fatigue risks with %CVL between 32.7%-34.4%. The ergonomic tool design enhances efficiency, reduces physical complaints, and supports worker productivity and well-being.